Fieldwork in Timor-Leste : understanding social change through practice - Nygaard-Christensen, Maj; Bexley, Angie (NIAS studies in Asian topics, 2017)
"This ground-breaking exploration of research methodologies in Timor-Leste brings together ten authors (veterans and early-career researchers) who have contributed to founding the field of Timor studies and who broadly represent a range of fieldwork practices and challenges from colonial times to the present day. Here, they introduce readers to their experiences of conducting anthropological, historical and archival fieldwork in this new nation. The volume further explores how researchers might examine processes of 'nation-making' without taking particular claims about what constitutes Timorese national identity for granted. Many chapters thus deal with how preconceptions can be challenged when actually carrying out ethnographic or historical research. The volume thus reflects and highlights the contestations and deliberations that have been symptomatic of the country's nation-building process." --